Microsoft to spammers go phish [e-mail security]. - Ross, P.E.
This paper compares the capabilities of two new e-mail security technologies specifically aimed at addressing the problem of spamming, especially phishing. On one hand is Microsoft's proposal, called Sender ID, and on the other is DomainKeys Identified Mail (DKIM) from Cisco Systems Inc. and Yahoo Inc. While both proposals feature similar e-mail verification capabilities, Microsoft's Sender ID has problems when it comes to forwarding messages as it is unable to tell whether forwarded mail is legitimate or spam. There is a proposal, however, to combine the features of both systems and using some complementary filters.
Keywords: Cisco Systems Inc; DomainKeys Identified Mail; Microsoft; Microsoft Corp; Sender ID technology; Yahoo Inc; E-mail verification; Forwarded mail; Spam; Unwanted e-mail.